Masked stereolithography of wollastonite-diopside glass-ceramics from novel silicone-based liquid feedstock - Elsayed, Hamada (2023)
Silicate bioceramics, including systems based on the simultaneous presence of wollastonite (CaSiO3) and diopside (CaMgSi2O6), are of great interest in bone tissue engineering applications, especially in form of variously shaped three-dimensional scaffolds, as determined by application of several additive manufacturing technologies. In this framework, silicone resins, properly modified with CaO- and MgO-based fillers and blended with photocurable acrylates, are attractive both as precursors and as feedstock for additive manufacturing technologies, including stereolithography. The use of powder fillers, however, may lead to issues with homogeneity or with printing resolution (owing to light scattering). The present paper aims at presenting the first results from a new concept of incorporation of CaO and MgO, relying on salts dispersed in emulsion within a photocurable silicone/acrylate blend. Direct firing at 1100 °C of printed scaffolds successfully produced wollastonite-diopside glass-ceramic scaffolds, with a very fine crystal distribution. The strength-to-density was tuned by operating either on the topology of scaffolds or on the firing atmosphere (passing from air to N2).